Respuesta :

First equation:

[tex]x^{\log_3x-4}=3^{-3}[/tex]

[tex]\log_3\left(x^{\log_3x-4}\right)=\log_33^{-3}[/tex]

[tex](\log_3x-4)\log_3x=-3\log_33[/tex]

[tex](\log_3x)^2-4\log_3x=-3[/tex]

[tex](\log_3x)^2-4\log_3x+3=0[/tex]

[tex](\log_3x-3)(\log_3x-1)=0[/tex]

[tex]\log_3x-3=0\text{ or }\log_3x-1=0[/tex]

[tex]\log_3x=3\text{ or }\log_3x=1[/tex]

[tex]3^{\log_3x}=3^3\text{ or }3^{\log_3x}=3^1[/tex]

[tex]x=27\text{ or }x=3[/tex]

Second equation:

[tex]x^{\log_2x}=16[/tex]

[tex]x^{\log_2x}=2^4[/tex]

[tex]\log_2\left(x^{\log_2x}\right)=\log_22^4[/tex]

[tex]\log_2x\log_2x=4\log_22[/tex]

[tex](\log_2x)^2=4[/tex]

[tex]\log_2x=\pm2[/tex]

[tex]2^{\log_2x}=2^{\pm2}[/tex]

[tex]x=2^2\text{ or }x=2^{-2}[/tex]

[tex]\boxed{x=4\text{ or }x=\dfrac14}[/tex]